An Autopsy Case of Anaplastic Pancreatic Ductal Carcinoma (Spindle Cell Type) Multiple Onset in the Pancreas - Hiroyuki Ito; Shin-ichiro Hiraiwa; Tomoko Sugiyama; Takuma Tajiri; Hisamichi Yoshii; Hideki Izumi; Yoko Yamaji; Motoki Kaneko; Shingo Tsuda; Hitoshi Ichikawa; Junko Nagata; Seiichiro Kojima; et al. (Case Reports in Oncology, 2019)
This is a case of a 75-year-old man who was diagnosed with anaplastic pancreatic ductal carcinoma (spindle cell type). His image findings showed pancreatic head cysts and pancreatic head, body, and tail tumors respectively. EUS-FNA was performed to the pancreatic head and pancreatic body tumors, and the same high atypical type cells suspected of cancer were obtained from either specimen, and finally total pancreatectomy was performed. On the specimen, there were 4 lesions in the pancreas; histology showed that the same anaplastic pancreatic ductal carcinoma (spindle cell type) was obtained from the pancreatic head cyst and the pancreatic tumors.